iPhone Advanced Projects - Mark, Dave (Apress, 2012)
As the fourth book in our series of iPhone Projects based on the work and experiences of iPhone, this volume takes on the more advanced aspects of iPhone development. The first generation of iPhone applications has hit the App Store, and now it's time to optimize performance, streamline the user interface, and make every successful iPhone app just that much more sophisticated.